Attitudes towards persons with disabilities vs. personality traits of Polish students - Radlińska, Iwona; Kożybska, Marta; Prajzner, Arkadiusz; Krzywoszański, Łukasz; Karakiewicz, Beata (Frontiers in Psychiatry, 2025)
ObjectiveThe study aimed to establish the relationship between attitudes towards persons with disabilities and personality traits among Polish students, and whether sociodemographic factors moderate this.MethodsA cross-sectional self-report online survey was conducted on 595 Polish students, aged 18–29, from different fields of study: 1) natural science and engineering technology; 2) social science and humanities; 3) medical and health sciences; 4) law, economics, and management. Polish adaptations of the scales were used in the study: Multidimensional Attitudes Scale Towards Persons With Disabilities (MAS) and the Ten Item Personality Inventory (TIPI).ResultsA significant correlation was demonstrated between attitudes towards individuals with physical disabilities and a range of personality traits, including agreeableness, extroversion, conscientiousness, and openness, among Polish students. The strongest attitude predictors were openness to experience, agreeableness, and extraversion, with correlation coefficients ranging from -0.06 to -0.19, -0.14 to -0.22, and -0.09 to -0.15, respectively. As scores increased in these personality traits, attitudes towards people with disabilities became more positive. However, conscientiousness (-0.07 to -0.09) and emotional stability (-0.02 to 0.12) were poor predictors. The supplementary analyses indicate that contact with a person with a disability and socio-demographic factors, such as gender, age, place of residence, mode, and field of study, assessment of one’s health, and material conditions, did not moderate the relationships between personality dimensions and attitudes towards persons with disability.ConclusionPolish students’ attitudes towards individuals with physical disabilities are associated with personality traits such as agreeableness, extraversion, conscientiousness, and openness. However, the strength of these relationships is relatively weak. This relationship is not moderated by contact with a person with a disability or sociodemographic factors. It seems that undertaking educational interventions to strengthen the indicated personality traits is particularly important. The results indicate the need for further research into factors that modulate attitudes towards persons with disabilities, including a theoretical deepening of the problem and cultural aspects.